Health circles for teleworkers: selective results on stress, strain and coping styles. - Konradt U; Schmook R; Wilm A; Hertel G (Health Education Research, 2000)
Telework is decentralized computer-mediated performance of work activities at a location distant from the employing organization. In order to improve well-being at such remote workplaces, we developed a health circle (HC) concept for teleworkers. Three HC sessions were conducted with a total of 17 teleworkers from diverse organizations and branches. The sessions were moderated by a professional facilitator, while the participants selected the discussion issues. Typical issues were technical problems at the home-based computer, time management, communication with supervisors, colleagues and customers, and feelings of isolation from the main company. Besides discussing these stress factors, participants developed concrete coping strategies based on the exchange of experiences and additional informational input by external experts. Process evaluation at the end of each meeting revealed that participants found the exchange of personal experiences and the informational input during the HCs very helpful, as well as the common development of coping strategies. Moreover, a questionnaire 2 months after the last HC session revealed that participants reported significantly more positive changes in typical stress factors than teleworkers in a control group. The implications of these results for preventive and corrective strategies of telework design are discussed.